2001
DOI: 10.1021/jo015709i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Metal-Ion Binding Properties of Monoazathiacrown Ethers

Abstract: Synthetic procedures for monoazathiacrown ethers were explored, and monoazatrithia-12-crown-4, monoazatetrathia-15-crown-5, and monoazapentathia-18-crown-6 were obtained in moderate yields by the reaction of bis(2-chloroethyl)amine with the appropriate dithiols in the presence of lithium hydroxide in THF. To evaluate metal-ion binding properties of the monoazathiacrown ethers by solvent extraction, lipophilic dodecyl and dodecanoyl groups were incorporated onto the monoazathiacrown ethers. The solvent extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…It can be seen that all polymer membranes based on 2,2 -thiodiethanethiol derivatives 15-17 with five sulfur atoms as ionophores gave excellent K pot AgJ against the examined interfering ions as compared to other ionophores, although compound 16 with the ring number of 22 showed a little bit better selectivity toward Ag + than compounds 15 and 17. These results are consistent with those reported previously showing that the selectivity of azathiacrown ethers to silver ions is proportional to the number of the sulfur atoms in the ring system [21,23]. It is interesting to note that the flexibility of the ring also has large effect on the selectivity Table 2 Potentiometric selectivity coefficients, log K pot AgJ , obtained with the separate solution method for o-NPOE-PVC (2:1) membranes based on ionophore 15-23 a .…”
Section: Characteristics Of the Ionophore-based Ag + -Isessupporting
confidence: 89%
“…It can be seen that all polymer membranes based on 2,2 -thiodiethanethiol derivatives 15-17 with five sulfur atoms as ionophores gave excellent K pot AgJ against the examined interfering ions as compared to other ionophores, although compound 16 with the ring number of 22 showed a little bit better selectivity toward Ag + than compounds 15 and 17. These results are consistent with those reported previously showing that the selectivity of azathiacrown ethers to silver ions is proportional to the number of the sulfur atoms in the ring system [21,23]. It is interesting to note that the flexibility of the ring also has large effect on the selectivity Table 2 Potentiometric selectivity coefficients, log K pot AgJ , obtained with the separate solution method for o-NPOE-PVC (2:1) membranes based on ionophore 15-23 a .…”
Section: Characteristics Of the Ionophore-based Ag + -Isessupporting
confidence: 89%
“…The white crude product was recrystallized from acetonitrile to give white crystals. [1,7,10,13,19,4,16] pentathiadiaza-cyclodocosine-6,16(7H,17H)-dione (5) A solution of 2,2¢-dithioethanthiol (4) (0.695 g, 4.51 mmol) in dry DMF (75 ml) in a dropping funnel and a solution of (3) (2.0 g, 4.51 mmol) in dry DMF (75 ml) in a dropping funnel were added simultaneously under stirring and dry argon gas to dry DMF (50 ml) containing anhydrous sodium carbonate (1.91 g, 18 mmol) over 1.5 h at room temperature with continuous stirring. After addition was completed, reaction mixture was stirred at room temperature for another 2 h. The reaction was monitored by thin layer chromatography [pentane-ethyl acetate (6:4)].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fluorescence microscopic imaging techniques can map the temporal and spatial distribution of mercuric ions within living cells. Recently, many fluorescent probes for Hg 2 + detection have been developed (that is, using small organic molecules, [19][20][21][22][23][24][25] DNAzymes, [26,27] protein, [28,29] gold nanoparticles, [30][31][32] and oligodeoxyribonucleotide-based probes [33] ), but only few Hg 2 + imaging studies have been reported. [34][35][36] Liu [34] and Chang [35] applied the mercury sensor to cultured HEK cells separately, and Shin et al [36] presented a rhodamine-based probe and obtained fluorescence images in living cells and zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…3,9-dithia-6-monoazaundecane (DMA) is chosen as the metal receptor [25,[45][46][47] because of its high selectivity toward Hg 2 + . We synthesized DMA-Cy and characterized it by 1 H NMR, 13 C NMR, and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%